Soil Thermal Balance Analysis for a Ground Source Heat Pump System in a Hot-Summer and Cold-Winter Region - Zhongchao Zhao; Rendong Shen; Weixian Feng; Yong Zhang; Yanrui Zhang (Energies, 2018)
As a renewable and high energy efficiency technology providing air conditioning and domestic hot water, the ground source heat pump system (GSHPS) has been extensively used worldwide in recent years. Compared with conventional systems, GSHPSs with heat recovery reject less heat into the soil and extract more heat from it, which can help reduce soil thermal imbalance in hot-summer and cold-winter regions. In this paper, conventional GSHPS, and GSHPS with different heat recovery ratios, in a typical city were compared based on thermal imbalance ratios, average soil temperatures and soil temperature increases. The transient system simulation software was used to simulate the operation performance of GSHPS. The thermal imbalance ratio and soil temperature decreased with increasing heat recovery ratio. After 20 years of operation, the soil thermal imbalance ratios of the GSHPS were 29.2%, 21.1%, 16%, and 5.2%, and the soil temperature rises were 8.78 °C, 5.25 °C, 3.44 °C, and 0.34 °C, while the heat recovery ratios were 0, 18%, 30% and 53%, respectively. Consequently, a GSHPS with heat recovery is a potentially efficient and economical approach for buildings in hot-summer and cold-winter regions.